Learning in the Pandemic Period: The Role of Teachers and Student Learning Motivation in Elementary Schools, Gorontalo - Wirna Tangahu (Newinera Publisher, 2022)
In 2020 Indonesia has become home to the outbreak of the pandemic that occurred in Wuhan. The pandemic, known as COVID-19, has not only attacked this country but all countries in the world. The spread of COVID-19 has had an unfavorable effect on all sectors of life, including education. Educational institutions have been paralyzed by moving learning that was originally carried out in schools and higher education institutions being transferred to homes. Students, students and students study and do activities at home following the ban on gathering outside the home. This situation requires teachers, especially in elementary schools, to adapt themselves and their environment to new situations. Teachers are forced to get acquainted with various online learning applications such as Zoom meating, goggle meating and several other applications. Teachers are required to be more innovative in creating online learning spaces that are more interesting and not boring. This effort is made so that students are motivated to learn so that their achievement does not decrease due to the pandemic situation.